2020
DOI: 10.20944/preprints202006.0105.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and Recycled Wastewater Irrigation: A Review of Implications

Abstract: Recycled wastewater is considered as a sustainable source of irrigation water. Despite commendable safety records, viral contamination of agricultural products has occurred the past causing disease outbreaks. This review examines the apprehension that the novel coronavirus (SARS-CoV-2) may also spread through recycled wastewater irrigation (RWI) industry. The novel SARS-CoV-2 is now perceived as an enteric pathogen, and has been found to remain stable in the wastewater for days. Mounting evidences also suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In general, there is lack of data on the effect of various wastewater treatment technologies applied at the UWTPs on SARS-CoV-2 as the first efforts were to firstly identify the virus in the influent of UWTPs. The removal efficiency of SARS-CoV-2 with traditional biological treatment processes such as the Conventional Activated Sludge (CAS) and the Membrane BioReactor (MBR) process, remains unclear due to the absence of experimental data (40[preprint]) . More specifically, the majority of the available data focuses on a large range of surrogate viruses of bacteriophages and laboratory-cultured viruses such as Enterovirus, Adenovirus and human polyomavirus JC, with a large variety of removal exhibited, from 0.9 to 5.8 logs [ 41 ].…”
Section: Main Considerations Related To the Development Of A Methodsolmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there is lack of data on the effect of various wastewater treatment technologies applied at the UWTPs on SARS-CoV-2 as the first efforts were to firstly identify the virus in the influent of UWTPs. The removal efficiency of SARS-CoV-2 with traditional biological treatment processes such as the Conventional Activated Sludge (CAS) and the Membrane BioReactor (MBR) process, remains unclear due to the absence of experimental data (40[preprint]) . More specifically, the majority of the available data focuses on a large range of surrogate viruses of bacteriophages and laboratory-cultured viruses such as Enterovirus, Adenovirus and human polyomavirus JC, with a large variety of removal exhibited, from 0.9 to 5.8 logs [ 41 ].…”
Section: Main Considerations Related To the Development Of A Methodsolmentioning
confidence: 99%
“…Currently, the potential route of the transmission of SARS-CoV-2 to humans in the wastewater-receiving environments via the reuse practice for agricultural irrigation has not been elucidated. Oliver et al [ 40 ] ([ preprint ]) reported that the selection of irrigation technique is critical for minimising the spread of the virus to the environment and suggested that alternative irrigation techniques, e.g. micro-irrigation, should be considered.…”
Section: Main Considerations Related To the Development Of A Methodsolmentioning
confidence: 99%
“…6,1014 Consequently, there has been a recent global interest in monitoring the dissemination of SARS-CoV-2 in municipal sewages, mainly for wastewater-based epidemiology (WBE). 3,1520 The implication that wastewater is a potential dissemination and infection route, has been also discussed, 13,2123 however, empirical evidences are still scarce. This is partially due to the current challenge of sample concentration and extraction methods, 24 required for precise virus quantification.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the amount usually removed (6-7 Log10) through the recycled water disinfection methods is much lower than viral particles shedding (up to 10 Log10) by infected people through sewage and greywater. Many researchers have been thought that these results showed an increased potential of contamination through the fecal-oral infection route from the water environment (Bhattacharjee, 2020; Chen et al, 2020b;Holshue et al, 2020;Medema et al, 2020;Oliver et al, 2020;Qu et al, 2020;Xiao et al, 2020a,b).…”
Section: Severe Acute Respiratory Syndrome (Sars-cov)mentioning
confidence: 96%